Math 10
Math 10
Math 10
Here I am again
1.) (x-1) ( x² - 5x + 6)
3.) (2x² - 5x + 3) (x - 3)
4.) x³ + 3x² - 4x - 12
5.) 2x⁴ + 7x³ - 4x² - 27x - 18
1.) (x-1) ( x² - 5x + 6)
Answer: (x-1)(x-2)(x-3)
Answer: (x+3)(x-2)(x-3)(x-3)= (x-3)²(x+3)(x+2)
3.) (2x² - 5x + 3) (x - 3)
4.) x³ + 3x² - 4x - 12
Answer: (2x+3)(x+3)(x+1)(x-2)
6. y=x³+x²-12x
7. y=-x⁴+16
8. y=2x⁴+8x³+4x²-8x-6
9. y=-x5+10x³-9x
10. y=2x⁴+7x³-4x²-27x-18
Answer;
6. y=x(x+4)(x-3)
7.y=(-x^2+4)(x^2+4)
8. y=2(x^2+3)(x^2-1)(2x^2+x+2)
9.y=-x(x-1)(x-9)
10. y=10(2x-1)(x+4)(3x-2)
0 = (x+4)(x+2)(x-1)(x-3) if any of the expressions in the parenthesis equal zero then y (the left-hand side) will equal
0. So isolate each expression
0 = x +4
x = -4
To get the x-intercept/s, you simply have to set your y value to 0. Then solve what value/s of x will result in y=0
To get the y-intercept/s, you simply have to set your x value to 0. Then solve what value/s of y will result in x=0
Now, to get the values of x for y = 0, we just have to make each factor 0. So,
x+4 = 0, means x = -4
x+2 = 0, means x = -2
x-1 = 0, means x = 1
x-3 = 0, means x = 3
This means that for the following values of x: -4, -2, 1, and 3, the value of y = 0. In the
relation to 0 column, of course, we also put y = 0. Remember that the x-axis is just the line
y=0, so for these values of x, the point is on the x-axis.
This is also the answer for question 1, but since it's asking for points, we write it in the (x,y)
notation: (-4,0), (-2,0), (1,0) and (3,0).
For question 2, it asks what we can say about the graph at x < -4. Since - 5<-4, and there is
no other zero of x that is less than -4, we can say that when x <-4, it is still above the x-axis,
because y at x=-5 is above the x-axis. This is because for the graph to be below or on the x-
axis, it has to pass through an x that makes the value of y = 0 first. Since there's none, there
is the same behavior there.
This is the same way we answer questions 3-6, by just taking the behavior at each point. So
before we answer this, let's complete the table first.
y(-3) = (-3+4)(-3+2)(-3-1)(-3-3) = (1)(-1)(-4)(-6) = -24, so y <0, and below the x-axis. Then, we
can use this point for question 3, and say "Below the x-axis" as well.
y(0) = (0+4)(0+2)(0-1)(0-3) = (4)(2)(-1)(-3) = 24, so y >0, and above the x-axis. We can use
this for question 4.
y(2) = (2+4)(2+2)(2-1)(2-3) = (6)(4)(1)(-1) = -24, so y <0, and below the x-axis. We can use
this for question 5.
y(4) = (4+4)(4+2)(4-1)(4-3) = (8)(6)(3)(1) = 144, so y>0, and above the x-axis. We can use this
for question 6.
polynomial function either falls or rises to the left continuously without end.
b.
1.
2.
3.
4.
x>1
5.
c.
end.
d.
the following:
degree: 3
degree: 4
degree: 10